Effect of protrusions on cathodic-arc-attachment mode in high-pressure arc discharges - Benilov, M. S. (2022)
It is shown via computer simulations that a protru sion on a thermionic arc cathode may dramatically change the pattern of steady-state modes of current transfer. This happens through a bifurcation of a special type occurring at certain geom etry of the cathode and may play a role in operation of electrodes of compact high-intensity discharge lamps.